1995
DOI: 10.1093/milmed/160.11.577
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cervical Smears in the Military Recruit Population

Abstract: Human papillomavirus is a common genital tract infection believed to be a causative agent of uterine cervical dysplasia. In a minority of cases, dysplasia progresses to squamous cell carcinoma. We reviewed the cervical smear reports for all female recruits who reported for training at Navy Recruit Training Center, Orlando, in calendar year 1993. During this period, 8,029 female recruits reported for training. We found that 24 recruits (0.30%) had a finding of high-grade squamous intra-epithelial lesion (HSIL);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, a study conducted in 1993 also reported a 3% prevalence rate of low-grade or high grade SIL among female military recruits. 45 An older study conducted among 332 female cadets with an average age of 22 years demonstrated that 5% had cervical cytology results consistent with low-grade or high grade SIL. 46 Based on the evidence presented, the prevalence of low-grade or high-grade SIL among military women is between 2.5% and 5%.…”
Section: Cervical Dysplasia and Human Papillomavirus Infectionmentioning
confidence: 99%
“…However, a study conducted in 1993 also reported a 3% prevalence rate of low-grade or high grade SIL among female military recruits. 45 An older study conducted among 332 female cadets with an average age of 22 years demonstrated that 5% had cervical cytology results consistent with low-grade or high grade SIL. 46 Based on the evidence presented, the prevalence of low-grade or high-grade SIL among military women is between 2.5% and 5%.…”
Section: Cervical Dysplasia and Human Papillomavirus Infectionmentioning
confidence: 99%
“…However, the prevalence of HGSIL in the United States can be estimated using two large cohorts. In one cohort, which contained 8026 patients in a military setting who underwent screening as part of their annual physical exam, 0.3% of the Pap smears showed HGSIL [8]. In the other cohort, the National Breast and Cervical Cancer Detection Program, in which women are screened annually at health department sites, HGSIL were evident in 1.1% of 100,500 Pap smears [9].…”
Section: Incidence Of Cervical Lesionsmentioning
confidence: 99%
“…A study on recruits showed a rising rate of disease with 8% affected in 1993, 25% in 1995 and 28.8% in 1996. 120,121 A history of sexually transmitted disease is common for both sexes in the Navy. The rate for pelvic inflammatory disease from self reported data in 1988 was 10.1/1000 women years for white women and 16.5/1000 women years for non-white women.…”
Section: General Gynecological Needsmentioning
confidence: 99%